Beyond Presence: Teachers’ Classroom Time and Professional Accountability (Research Journal on Multi-disciplinary Issues, 2026)
This study examines teachers' classroom time utilization and professional accountability in Nepalese public schools, especially in the remote part of Terai region. The purpose behind this study is to investigate the widespread concern of teachers failing to utilize the full 45-minute class period for instructional purposes. Through questionnaires administered to 20 teachers and head teachers, supplemented by public discourse analysis and literature review, the research explores factors affecting professional commitment and time investment. Findings reveal teachers possess a sophisticated understanding of professionalism and recognize devotion's importance, yet systemic conditions-including inadequate compensation, political interference, weak institutional leadership, and social devaluation-constrain actualization of professional ideals. The pattern of inadequate time utilization reportedly intensified following democracy's restoration in 1990, when political affiliations began compromising professional commitments. The study concludes that meaningful improvement requires comprehensive systemic reform addressing both individual accountability and institutional support, recognizing the complex interplay of economic, social, political, and institutional factors shaping teacher performance and educational outcomes.